FRUIT ORIENTATION ALTERS THE QUALITY OF LITCHI (LITCHI CHINENSIS SONN.) UNDER THE AGRO-CLIMATIC CONDITIONS OF EASTERN INDIA - LAL, NARAYAN; NATH, VISHAL (Innovare Journal of Agricultural Sciences, 2021)
Objective: The experiment was conducted on ten litchi cultivars, namely; Purbi, Bedana, Lal Bombay, Mandaraji, Calcuttia, Late Bedana, Trikolia, Dehradoon, Dehrarose, and Seedless No. 2 to assess the physical and chemical composition of fruit as affected by fruit orientation on the tree. Methods: Fruits were picked both from the lower and upper half portion of the tree at fully ripened stage and physio-chemical attributes were analyzed. Results: The result indicated that fruits at lower half portion were not only heavy in weight but also had more percentage of total acidity. However, stone weight, ascorbic acid content, and total sugars were found to be more in fruits collected from the upper half portion of the tree. Conclusion: It can be suggested that picking should be started from those fruits which are positioned at the lower half portion of the tree to collect fruits of superior quality.